Effects of nitric oxide and arginine vasopressin on sodium intake induced by central angiotensin II. Part 2 - Saad, Wilson Abrão [UNESP]; Guarda, Ismael Francisco Motta Sigueira; Carmago, Luis Antonio de Arruda [UNESP]; dos Santos, Talmir Augusto Faria Brizola; Saad, William Abrão (Science Alert, 2007)
We study the effects of angiotensin receptors antagonists, arginine vasopressin receptor antagonist, L-arginine and L-NAME, injected into supraoptic nucleus of the hypothalamus (SON) on sodium intake induced by the injection of angiotensin II (ANGII). Holtzman rats weighing 200-250 g with canulae implanted into the SON were used. The drugs were injected in 0.5 μL over 30-60 sec. Sodium intake after injection of saline SAL+SAL 0.15 M NaCl was 0.10±00.1 mL 2 h -1; SAL+ANGII injected into SON increased sodium intake. Losartan injected prior to ANGII into SON decreased sodium intake induced by ANGII. PD123319 injected prior to ANGII produced no changes in sodium intake induced by ANGII. AVPA receptor V 1 antagonist injected prior to ANGII reduced sodium intake with a less intensity than losartan. L-arginine injected prior to ANGII decreases sodium intake at a same intensity than losartan. L-NAME injected prior to ANGII potentiated sodium intake induced by ANGII. Losartan injected simultaneously with L-arginine prior to ANGII blocked the natriorexigenic effect of ANGII. These results confirm the importance of SON in the control of sodium intake. Also suggest that both AT 1 and arginine vasopressin V 1 receptors interact with nitrergic pathways within the SON influencing the sodium metabolism by changing sodium appetite induced by ANGII. © 2007 Asian Network for Scientific Information.
Keywords: Angiotensin antagonists; Nitric oxide; Receptors; Sodium metabolism; Supraoptic nucleus; Vasopressin antagonist receptor; 1 (4 dimethylamino 3 methylbenzyl) 5 diphenylacetyl 4,5,6,7 tetrahydro 1h imidazo[4,5 c]pyridine 6 carboxylic acid; angiotensin 1 receptor; angiotensin II; angiotensin receptor antagonist; arginine; argipressin; argipressin receptor; losartan; n(g) nitroarginine methyl ester; nitric oxide; sodium; sodium chloride; animal experiment; animal model; animal tissue; body weight; controlled study; hypothalamus; nonhuman; protein interaction; rat; sodium appetite; sodium intake; sodium metabolism; Sprague Dawley rat; supraoptic nucleus; Rattus